2022
DOI: 10.3390/children9071019
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication Efficacy of Therapy Based on the Antimicrobial Susceptibility in Children with Gastritis and Peptic Ulcer in Mekong Delta, Vietnam

Abstract: Background: The efficacy of Helicobacter pylori (H. pylori) eradication therapy for children is currently low, and antibiotic resistance is a significant cause of treatment failure. The purpose of this study was to evaluate the H. pylori eradication efficacy of therapy based on antimicrobial susceptibility in pediatric patients with gastritis and peptic ulcer. Methods: This study was conducted at Can Tho Children’s Hospital and Can Tho University of Medicine and Pharmacy Hospital between March 2019 and April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…No strain was resistant to all five tested antibiotics. Our results are similar to other studies in Vietnam and around the world carried out in recent years [ 14 , 15 , 21 , 25 , 26 ]. However, the rate of antibiotic resistance is higher than in another study conducted in Vietnam in 2008.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No strain was resistant to all five tested antibiotics. Our results are similar to other studies in Vietnam and around the world carried out in recent years [ 14 , 15 , 21 , 25 , 26 ]. However, the rate of antibiotic resistance is higher than in another study conducted in Vietnam in 2008.…”
Section: Discussionsupporting
confidence: 92%
“…This study also evaluated dual resistance with AMX–CLR, AMX–MTZ, AMX–LEV, CLR–MTZ, and MTZ–TET to help clinicians see the risk of failure in eradicating H. pylori when choosing the corresponding empiric regimen. Multidrug resistance was defined as the strain being resistant to three or more antibiotics [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study performed in Wenzhou, Zhejiang province, China, when CLA resistance reached 26.12%, the efficacies of triple therapy and bismuth-containing quadruple therapy based on the antibiotic susceptibility test were 67.32% and 68.49%, respectively ( Pan et al, 2020 ). Studies in Vietnam revealed increased resistance to CLA, with rates of 50.9% in 2006 ( Le et al, 2022 ), 84.6% in 2012 ( Le et al, 2022 ), 92.1% in 2021 ( Van Thieu et al, 2021 ), and 81% in 2022 ( Borka et al, 2023 ). The success rate of treatment based on antimicrobial testing is 75% in Vietnam ( Nguyen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data collection was conducted among healthcare professionals at a public hospital in Vinh Long province, Vietnam. Vinh Long province is located in the Mekong Delta region, 26 approximately 135 km southwest of Ho Chi Minh City. 27 Vinh Long’s economy is growing rapidly compared to that of other provinces in Vietnam.…”
Section: Methodsmentioning
confidence: 99%